COVID-19 AND ITS IMPACT ON DISINFORMATION AND FAKE NEWS - Mikiashvili, Salome (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: the purpose of the study is to critically evaluate the disinformation spread by different state interested groups during the corona virus pandemic and it’s concequences. The methodological basis of the research comprises philosophical, ideological, general scientific and special methods. Results: Corona Virus Pandemic was so unexpectable for World. Coronavirus gave rise to a new online era. The world has shifted to existence in the virtual mode, which in turn caused new difficulties. the more the disinformation will substitute the authoritative legal sources the greatest threat it becomes for public health and political order. The author exemines the effectivness of the measures taken by the US and EU countries taken during Corona virus pandemic to combat spread of disinformation. Discussion: raising awareness about disinformation and Covid-19 to reduce spread of fake news, search for actions to be taken while dealing with the spread of disinformation.